PERFORMANCE TRANSFORMATION THROUGH LEADERSHIP: - Zebua, Martin; Chamid, Abdul (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research explores leadership's role in improving employee performance in a CA company engaged in printing. Using a qualitative approach, the research involved in-depth interviews with five employees to understand how leaders can motivate and create a productive work environment. The results indicated that effective leadership involves open communication and support for individual development so each employee feels valued and motivated to contribute to their full potential. Leaders who are sensitive to employees' needs can identify hidden potential within the team, which contributes to improved overall performance. The research also identified challenges that leaders face, such as a lack of morale among employees and negative peer influence, which can hinder productivity. Leaders need to create a positive and inclusive work atmosphere and provide fair rewards to boost motivation. The findings not only provide insights for leaders in CA but can also serve as a reference for other organizations looking to optimize employee performance through the right leadership approach. This research confirms the important role of leadership in creating a harmonious and accomplished team in the work environment. Keywords: Effective Leadership; Employee Performance; Motivation; Communication